Small rna-seq reveals novel regulatory components for apomixis in paspalum notatum - Ortiz, Juan Pablo Amelio (2019)
Background: Apomixis is considered an evolutionary deviation of the sexual reproductive pathway leading to the generation of clonal maternal progenies by seeds. Recent evidence from model and non-model species suggested that this trait could be modulated by epigenetic mechanisms involving small RNAs (sRNAs). Here we profiled floral sRNAs originated from apomictic and sexual Paspalum notatum genotypes in order to identify molecular pathways under epigenetic control that might be involved in the transition from sexuality to agamospermy. Results: The mining of genes participating in sRNA-directed pathways from floral Paspalum transcriptomic resources showed these routes are functional during reproductive development, with several members differentially expressed in apomictic and sexual plants. Triplicate floral sRNA libraries derived from apomictic and a sexual genotypes were characterized by using high-Throughput sequencing technology. EdgeR was apply to compare the number of sRNA reads between sexual and apomictic libraries that map over all Paspalum floral transcripts. A total of 1525 transcripts showed differential sRNA representation, including genes related to meiosis, plant hormone signaling, biomolecules transport, transcription control and cell cycle. Survey for miRNA precursors on transcriptome and genome references allowed the discovery of 124 entities, including 40 conserved and 8 novel ones. Fifty-six clusters were differentially represented in apomictic and sexual plants. All differentially expressed miRNAs were up-regulated in apomictic libraries but miR2275, which showed different family members with opposed representation. Examination of predicted miRNAs targets detected 374 potential candidates. Considering sRNA, miRNAs and target surveys together, 14 genes previously described as related with auxin metabolism, transport and signaling were detected, including AMINO ACID/AUXIN PERMEASE 15, IAA-AMIDO SYNTHETASE GH3-8, IAA30, miR160, miR167, miR164, miR319, ARF2, ARF8, ARF10, ARF12, AFB2, PROLIFERATING CELL FACTOR 6 and NITRATE TRANSPORTER 1.1. Conclusions: This work provides a comprehensive survey of the sRNA differential representation in flowers of sexual and apomictic Paspalum notatum plants. An integration of the small RNA profiling data presented here and previous transcriptomic information suggests that sRNA-mediated regulation of auxin pathways is pivotal in promoting apomixis. These results will underlie future functional characterization of the molecular components mediating the switch from sexuality to apomixis.